2020
DOI: 10.1101/2020.08.12.20173849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Obesity and Smoking as Risk Factors for Invasive Mechanical Ventilation in COVID-19 Respiratory Failure: a Retrospective, Observational Cohort Study

Abstract: Purpose: To describe the trajectory of respiratory failure in COVID-19 and explore factors associated with risk of invasive mechanical ventilation (IMV). Materials and Methods: A retrospective, observational cohort study of 112 inpatient adults diagnosed with COVID-19 between March 12 and April 16, 2020. Data were manually extracted from electronic medical records. Multivariable and Univariable regression were used to evaluate association between baseline characteristics, initial serum markers and the outcome… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…A study in Iran showed that among 193 confirmed COVID-19 patients, more than half of cigarette smokers and 40% of waterpipe smokers reported their COVID-19 symptoms as severe compared to 22% of never-smokers [34]. In a retrospective study, an observational cohort study of 112 in-patient adults, diagnosed with COVID-19, between March 12 and April 16, 2020, in Los Angeles, smoking history along with obesity and elevated inflammatory markers was associated with an increased need for invasive mechanical ventilation in patients with COVID-19 [35]. Another retrospective cohort study, conducted between February 24, 2020 and April 20, 2020 in Kuwait indicated that asthma, smoking and elevated procalcitonin levels correlated significantly with mortality in COVID-19 patients [36].…”
Section: Resultsmentioning
confidence: 99%
“…A study in Iran showed that among 193 confirmed COVID-19 patients, more than half of cigarette smokers and 40% of waterpipe smokers reported their COVID-19 symptoms as severe compared to 22% of never-smokers [34]. In a retrospective study, an observational cohort study of 112 in-patient adults, diagnosed with COVID-19, between March 12 and April 16, 2020, in Los Angeles, smoking history along with obesity and elevated inflammatory markers was associated with an increased need for invasive mechanical ventilation in patients with COVID-19 [35]. Another retrospective cohort study, conducted between February 24, 2020 and April 20, 2020 in Kuwait indicated that asthma, smoking and elevated procalcitonin levels correlated significantly with mortality in COVID-19 patients [36].…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of the patients in the included studies was 54.10 years. Nineteen studies defined outcomes as disease severity 22 , 27 30 , 37 39 , 42 , 43 , 46 50 , 58 , 60 , 62 , 63 . Seventeen studies defined outcomes as death 21 , 33 , 40 , 44 , 45 , 51 57 , 59 , 65 68 .…”
Section: Resultsmentioning
confidence: 99%
“…All studies defined smoking status as current smoker. Eleven studies included former smokers and current smokers 22 , 33 , 43 , 44 , 47 , 57 , 58 , 61 63 , 67 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted March 11, 2021. ; https://doi.org/10.1101/2021.03.09.21253206 doi: medRxiv preprint themselves are associated with increased pro-inflammatory cytokine levels and may represent independent risk factors for severe COVID-19 (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%